(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Two species of Euphorinae (Hymenoptera: Braconidae) have been described and illustrated from Bangladesh. The species are: Mateorus erratus Achterberg, 1997 and Perilitus lateropus Achterberg, 1997. These two species are new record to the fauna of Bangladesh. Mateorus erratus and Perilitus lateropus were collected from Tangail and Dhaka districts, respectively. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13405 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):45-52, 2008